A distributed stochastic approximation algorithm for stochastic LQ control with unknown uncertainty. (May 2023) - Zhang, Zhaorong; Xu, Juanjuan; Li, Xun
Abstract: This paper studies a discrete-time stochastic control problem with linear quadratic criteria over an infinite-time horizon. We focus on control systems whose system matrices are associated with random parameters involving unknown statistical properties. We design a distributed stochastic approximation algorithm to tackle the Riccati equation and derive the optimal controller stabilizing the system. The convergence analysis is provided.